1998
DOI: 10.1177/0145482x9809200508
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Technology in Programs for Students with Visual Impairments in Florida

Abstract: Teachers of students with visual impairments in Florida were surveyed to determine their use of various types of access technologies. Each category of device, with the exception of refreshable braille devices, was used by at least 25 percent of the teachers. The majority stated that they were not familiar with most of the devices listed and had difficulty acquiring the training needed to learn devices well enough to teach the students to use them. On the basis of these findings, recommendations for preservice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…(i.e., west, midwest, northeast, south) (Abner & Lahm, 2002;Behrmann, 1993;Derer, Polsgrave, & Rieth, 1996;Howard, 1992;Kapperman, Sticken, & Heinze, 2002;Lesar, 1998;McGregor & Pachuski, 1996;Wahl, 2004), collectively they fail to provide the same information for each of those regions. Several studies involve students from only two of the disability categories found in IDEIA 2004 (Abner & Lahm, 2002;Corn & Wall, 2002;Edwards & Lewis, 1998;Kapperman et al, 2002;Skellenger, 1999;Smith, Geruschat, & Huebner, 2004;Wehmeyer, 1998Wehmeyer, , 1999. Secondary students are virtually ignored (Abner & Lahm, 2002;Edwards & Lewis, 1998;McGregor & Pachuski, 1996;Skellenger, 1999;Wehmeyer, 1998Wehmeyer, , 1999.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(i.e., west, midwest, northeast, south) (Abner & Lahm, 2002;Behrmann, 1993;Derer, Polsgrave, & Rieth, 1996;Howard, 1992;Kapperman, Sticken, & Heinze, 2002;Lesar, 1998;McGregor & Pachuski, 1996;Wahl, 2004), collectively they fail to provide the same information for each of those regions. Several studies involve students from only two of the disability categories found in IDEIA 2004 (Abner & Lahm, 2002;Corn & Wall, 2002;Edwards & Lewis, 1998;Kapperman et al, 2002;Skellenger, 1999;Smith, Geruschat, & Huebner, 2004;Wehmeyer, 1998Wehmeyer, , 1999. Secondary students are virtually ignored (Abner & Lahm, 2002;Edwards & Lewis, 1998;McGregor & Pachuski, 1996;Skellenger, 1999;Wehmeyer, 1998Wehmeyer, , 1999.…”
mentioning
confidence: 99%
“…Several studies involve students from only two of the disability categories found in IDEIA 2004 (Abner & Lahm, 2002;Corn & Wall, 2002;Edwards & Lewis, 1998;Kapperman et al, 2002;Skellenger, 1999;Smith, Geruschat, & Huebner, 2004;Wehmeyer, 1998Wehmeyer, , 1999. Secondary students are virtually ignored (Abner & Lahm, 2002;Edwards & Lewis, 1998;McGregor & Pachuski, 1996;Skellenger, 1999;Wehmeyer, 1998Wehmeyer, , 1999. All but one of the studies (Kapperman et al, 2002) overlooks influences of community type (i.e., rural, urban, suburban) on AT use.…”
mentioning
confidence: 99%
“…The technology is one of the strongest allies to the visually impaired persons in overcoming the negative effects of visual impairment [18]. The technology is related to successful education and positive change in attitudes and has potential in reducing the influence of certain negative consequences brought by visual impairment.…”
Section: Models Of Assistive Technology Systemsmentioning
confidence: 99%
“…With the increasing emphasis on evidence-based practices in special education, it is important to ask whether the use of computers and the Internet by K-12 students with visual impairments has positive effects on the students' education. Although it is seemingly true and believed by many professionals (Abner & Lahm, 2002;Douglas, 2001;Edwards & Lewis, 1998), is there any empirical evidence to support this assumption?…”
mentioning
confidence: 99%